2001
DOI: 10.1103/physrevd.64.104015
|View full text |Cite
|
Sign up to set email alerts
|

Holography and brane cosmology in domain wall backgrounds

Abstract: We consider a class of domain-wall black hole solutions in the dilaton gravity with a Liouville-type dilaton potential. Using the surface counterterm approach we calculate the stress-energy tensor of quantum field theory (QFT) corresponding to the domain-wall black hole in the domain-wall/QFT correspondence. A brane universe is investigated in the domain-wall black hole background. When the tension term of the brane is equal to the surface counterterm, we find that the equation of motion of the brane can be ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 42 publications
1
42
0
Order By: Relevance
“…Klemm in [19] found supersymmetric solution in the four dimensional gauged N = 4, SU (2)×SU (2) supergarvity; Refs. [14,20,22,23] investigated domain wall solutions with k = 0 in Einstein-dilaton theory with a Liouville-type potential; Cvetic et al in [21] found a domain wall solution with k = 0 in an Einstein-Maxwell-dilaton theory with special coupling parameters a = b = 2/p in (2.27); for more recent discussions on the non-asymptotically AdS/dS solutions with k = 1 in four dimensional Einstein-Maxwell-dilaton theory without dilaton potential see [24,25]; other related discussions see [28].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Klemm in [19] found supersymmetric solution in the four dimensional gauged N = 4, SU (2)×SU (2) supergarvity; Refs. [14,20,22,23] investigated domain wall solutions with k = 0 in Einstein-dilaton theory with a Liouville-type potential; Cvetic et al in [21] found a domain wall solution with k = 0 in an Einstein-Maxwell-dilaton theory with special coupling parameters a = b = 2/p in (2.27); for more recent discussions on the non-asymptotically AdS/dS solutions with k = 1 in four dimensional Einstein-Maxwell-dilaton theory without dilaton potential see [24,25]; other related discussions see [28].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Indeed, in the literature, for example, see Refs. [15]- [23], some exact solutions of the action (1.4) have been found in some special cases. These solution are asymptotically neither AdS nor dS, different from those (1.2) which are asymptotically AdS or dS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-asymptotically flat/AdS black hole space-times have been actively studied for possible extensions of holography [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96]. The usual notions of thermodynamic mass, thought of as enthalpy of a space-time, akin to an AdS black hole go through for more general backgrounds.…”
Section: Introductionmentioning
confidence: 99%